Assessment of local wood species used for the manufacture of cookware and the perception of chemical benefits and chemical hazards associated with their use in Kumasi, Ghana - Mensah John Kenneth; Adei Evans; Adei Dina; Owusu Ansah Gwendolyn (BMC, 2012)
Abstract Background Historical proven wood species have no reported adverse health effect associated with its past use. Different historical proven species have traditionally been used to manufacture different wooden food contact items. This study uses survey questionnaires to assess suppliers', manufacturers', retailers' and consumers' (end-users') preferences for specific wood species, to examine the considerations that inform these preferences and to investigate the extent of awareness of the chemical benefits and chemical hazards associated with wooden food contact material use. Methods Through the combined use of a cross sectional approach and a case study design, 25 suppliers, 25 manufacturers, 25 retailers and 125 consumers (end-users) of wooden food contact materials in four suburbs in Kumasi Metropolitan Area (Anloga junction, Ahinsan Bus Stop, Ahwia-Pankrono and Race Course) and Ashanti Akyim Agogo in the Ashanti Akyim North District of the Ashanti Region were administered with closed ended questionnaires. The questionnaires were prepared in English, but local language, Twi, was used to translate and communicate the content of the questionnaire where necessary. Results Suppliers', manufacturers' and retailers' preferences for specific wood species for most wooden cookware differed from that of consumers (end-users). But all respondent groups failed to indicate any awareness of chemical benefits or chemical hazards associated with either the choice of specific wood species for specific wooden cookware or with the general use of wooden food contact materials. The lack of appreciation of chemical benefits or hazards associated with active principles of wooden cookware led to heavy reliance of consumers (end-users) on the wood density, price, attractive grain pattern and colour or on the judgement of retailers in their choice of specific species for a wooden cookware. Conclusion This study contributes some practical suggestions to guide national policy development on improvement in quality of available wooden food contact materials in Ghana.